"A Barbie agora é preta, travesti e engordou": uma análise crítica e interseccional do discurso e das escolhas de transitividade em letras de rap da Bixarte - Lima, Leonardo Adriano Eugênio de (2023)
This research is inserted in the research field of Applied Linguistics Transviada (BEZERRA, 2023) and, aims to investigate to what extent the discourses produced by the artist Bixarte, in her rap lyrics, create, reinforce, or destabilize normative representations of gender identities and sexuality (BENTO, 2017), race and social class (ALMEIDA, 2019; NASCIMENTO, 2016; SOUZA, 2021). The research was developed in an inter/transdisciplinary way, considering the theoretical and methodological contributions of Critical Discourse Analysis, specifically the three-dimensional model proposed by Fairclough (1992, 2001, 2003) in dialogue with the Transitivity System, a textual analysis tool proposed in Systemic-Functional Grammar developed by Halliday and Matthiessen (2014), emphasizing the intersectional perspective (CRENSHAW, 2002; AKOTIRENE; 2019; BUENO, 2020). In methodological terms, this research presents itself in a perspective of qualitative nature and of interpretative character. The analyzed data were taken from two songs written by the artist. The first track is “Revolution” from the EP Revolution and the second track is “Gordo Week”, from Mixtape Faces. The results of the analyzes revealed a great mobilization of figures of physical, mental and relational actions in both songs, allowing access to the discursive and social practices that evidenced the dispute for power between the discourses articulated in the artist's songs. Notably, the discursive acts performed by the artist propose the deconstruction of institutions and hegemonic structures constituted from the knowledge, beliefs and ways of life of the European cis-hetero white man, who, through colonial imposition, establishes norms that end with the silencing, the exclusion, erasure and death of identities of black, fat and/or gay or queer people, lesbians, transvestites, as well as transgender women and men who, often jointly, occupy the peripheral spaces of cities. In addition, the artist's discourse configures a new social representation for these bodies, conferring the emancipatory power of language.